Celastrol inhibits proliferation and induces chemosensitization through down-regulation of NF-κB and STAT3 regulated gene products in multiple myeloma cells - Kannaiyan, R.; Hay, H.; Rajendran, P.; Li, F.; Shanmugam, M.; Vali, S.; Abbasi, T.; Kapoor, S.; Sharma, A.; Kumar, Alan Prem; Chng, W.; Sethi, G. (John Wiley & Sons, 2011)
BACKGROUND AND PURPOSE: Activation of pro-inflammatory transcription factors NF-κB and signal transducer and activator of transcription 3 (STAT3) is one of the major contributors to both pathogenesis and chemoresistance in multiple myeloma (MM), which results in high mortality rate. Thus, in the present study, we investigated whether celastrol could suppress the proliferation and induce chemosensitization of MM cells by interfering with NF-κB and STAT3 activation pathways. EXPERIMENTAL APPROACH: The effects of celastrol were investigated using both a virtual predictive tumour cell system and different MM cell lines resistant to doxorubicin, melphalan and bortezomib. KEY RESULTS: Celastrol inhibited the proliferation of MM cell lines regardless of whether they were sensitive or resistant to bortezomib and other conventional chemotherapeutic drugs. It also synergistically enhanced the apoptotic effects of thalidomide and bortezomib. This correlated with the down-regulation of various proliferative and anti-apoptotic gene products including cyclin D1, Bcl-2, Bcl-xL, survivin, XIAP and Mcl-1. These effects of celastrol were mediated through suppression of constitutively active NF-κB induced by inhibition of IκBα kinase activation; and the phosphorylation of IκBα and of p65. Celastrol also inhibited both the constitutive and IL6-induced activation of STAT3, which induced apoptosis as indicated by an increase in the accumulation of cells in the sub-G1 phase, an increase in the expression of pro-apoptotic proteins and activation of caspase-3. CONCLUSIONS AND IMPLICATIONS: Thus, based on our experimental findings, we conclude that celastrol may have great potential as a treatment for MM and other haematological malignancies.